Предмет: Алгебра,
автор: Настя15052001
Упростить................
Приложения:
Ответы
Автор ответа:
0
1)(∛x²y²+x∛y)/(x∛y+y∛x)-1=(∛x²y²+x∛y-x∛y-y∛x)/∛xy(∛x²+∛y²)=
=(∛x²y²-y∛x)/∛xy(∛x²+∛y²)=∛xy²(∛x-∛y)/∛xy(∛x²+∛y²)=
=∛y(∛x-∛y)/∛x²+∛y²)
2)∛x²/∛y²+∛x/∛y +1=(∛x²+∛xy+∛y²)/∛y²
3)[(y-x)/y]^-1=y/(y-x)
4)∛y(∛x-∛y)/∛x²+∛y²) *(∛x²+∛xy+∛y²)/∛y² *y/(y-x)=
=(x-y)∛y²/(∛x²+∛y²)(y-x)=-∛y²/(∛x²+∛y²)
=(∛x²y²-y∛x)/∛xy(∛x²+∛y²)=∛xy²(∛x-∛y)/∛xy(∛x²+∛y²)=
=∛y(∛x-∛y)/∛x²+∛y²)
2)∛x²/∛y²+∛x/∛y +1=(∛x²+∛xy+∛y²)/∛y²
3)[(y-x)/y]^-1=y/(y-x)
4)∛y(∛x-∛y)/∛x²+∛y²) *(∛x²+∛xy+∛y²)/∛y² *y/(y-x)=
=(x-y)∛y²/(∛x²+∛y²)(y-x)=-∛y²/(∛x²+∛y²)
Похожие вопросы
Предмет: Физика,
автор: verachurkina02
Предмет: История,
автор: 20mila6ka08
Предмет: Английский язык,
автор: chachatryanariana
Предмет: Геометрия,
автор: Shaaaaa63